Estimated Cost-Effectiveness of Implementing a Statewide Tranexamic Acid Protocol for the Management of Suspected Hemorrhage in the Prehospital Setting. (3rd April 2023) - Hubble, Michael W.; Renkiewicz, Ginny K.; Schiro, Sharon; Van Vleet, Lee; Houston, Sara
Abstract: Introduction: Hemorrhage is responsible for up to 40% of all traumatic deaths. The seminal CRASH-2 trial demonstrated a reduction in overall mortality following early tranexamic acid (TXA) administration to bleeding trauma patients. Following publication of the trial results, TXA has been incorporated into many prehospital trauma protocols. However, the cost-effectiveness of widespread TXA adoption by EMS is unknown. Objective: To estimate the cost-effectiveness of statewide implementation of a TXA protocol. Methods: The North Carolina Trauma Registry was queried to identify potential TXA patients using the a priori criteria of age ≥18 years, suspected hemorrhage, penetrating or blunt injury, and prehospital blood pressure <90 mmHg and heart rate >110 bpm. Using life tables adjusted for age, sex, and race, and the absolute risk reductions in mortality with early TXA administration reported in the literature, the life-years gained were calculated for each potential life saved. Implementation costs consisted of initial stocking, training, and replacement costs. Projected reduction in hospitalization costs were based on estimates reported in the literature. Economic analyses were conducted from societal and state EMS system perspectives. To assess the robustness of the model, univariate and bivariate sensitivity analyses were performed on selected input variables. Results: Based on the TXA inclusionary criteria, 159 patients could potentially receive TXA per year. In the base-case scenario with a projected absolute mortality reduction of 3%, an additional 4.8 lives per year in NC would be saved, with an estimated 191 total life-years gained. The statewide implementation and operation cost was 305, 122 in year 1, and continued operating costs were 6, 042 in years 2 and 3, yielding a cost per life saved of 63, 967 in year 1 and 1, 267 in years 2 and 3. The cost per life-year gained was 1, 595 in year 1 and 32 in years 2 and 3. Annual hospitalization costs would potentially be reduced by 1, 828, 072. Conclusion: Previous studies have demonstrated the clinical effectiveness of early TXA administration to patients with hemorrhage. Our modeling of the financial implications and clinical benefits of implementing a statewide TXA protocol suggests that prehospital TXA is a cost-effective treatment.